Model Pembelajaran Take and Give dalam Meningkatkan Keterampilan Sosial - Royan Rosyadi (Departement of Mathematics Education, 2024)
This research aims to improve students' social skills by using the take and give learning model in social science learning for students. What is the effect of implementing the take and give type cooperative learning model in improving students' social skills? The method used in this research is classroom action which consists of three cycles, each cycle includes planning, implementation, observation and reflection, data collection techniques using observation on the affective aspect, data analysis methods using descriptive analysis, the results of this research show improvements in the cycle II and III with increasing attainment of social skills indicators, namely communication, interaction, participation and cooperation indicators.